The mechanical response of dry-process polymer wastes modified asphalt under ageing and moisture damage - Radeef H.R.; Hassan N.A.; Katman H.Y.; Mahmud M.Z.H.; Abidin A.R.Z.; Ismail C.R. (Elsevier Ltd, 2023)
Asphalt concrete; Concrete mixtures; Deformation; Lime; Moisture; Rubber; Tensile strength; Long-term aging; Modified asphalts; Moisture conditioning; Moisture conditioning, permanent deformation; Moisture damage; Permanent deformations; Plastics waste; Polymer wastes; Rubberized asphalt; Waste plastic; Mixtures